An exploration of private college students’ perceptions of the concept of ethical behaviour in academic work in China - Chen, Lin; Saharuddin, Norzihani; Muhamad, Mohd Mokhtar (SAGE Publications, 2024)
In China, unethical behaviour in academic work is regarded as a severe problem in higher education that has the potential to stifle the growth of creativity and innovation. However, research on ethical behaviour in academic work is still uncommon in private colleges, particularly from the perspective of undergraduate students. As a result, the purpose of this qualitative study is to explore Chinese private college students’ perceptions of the concept of ethical behaviour in academic work. Bandura’s social cognitive theory examined and analysed students’ perceptions and perspectives on ethical behaviour in academic work. To assess participants’ perceptions, one-on-one semi-structured interview, focus group discussion, and reflection in narrative story writing were conducted. The study sample consisted of five participants from three private colleges in three cities in China. According to the content analysis findings, Chinese private college students’ perspectives of the concept of ethical behaviour in academic work are social and professional academic ethics and academic malpractices. Meanwhile, Chinese private college students’ perspectives of the concept of ethical behaviour in academic work are academic misconduct and academic professional standards. The results have practical significance for helping private college students overcome ethical behaviour problems in academic work.